MANAJEMEN PEMASARAN PONDOK PESANTREN - El Wahyu, Muhammad Zaini (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study was to describe the natural setting, marketing planning for Islamic boarding schools services, organizing Islamic boarding schools services marketing, implementing Islamic boarding schools services marketing, supervision of Islamic boarding schools services marketing, Islamic boarding schools marketing mix strategy, and results of service marketing at the Nuruzzaman Islamic Boarding School, Bandung City.The method used in this research is descriptive qualitative method. Data collection techniques were carried out using interviews, observation, documentation studies and copying. Whereas in analyzing the data used is purely descriptive interpretation and data validity tests are carried out by extending participation, observation persistence, negative case analysis, adequacy of references, detailed descriptions, triangulation, peer examination, member checking and auditing.The results of this study indicate that Service Marketing Management at the Nuruzzaman Islamic Boarding School in Bandung City in terms of marketing is an educational institution that predominantly uses indirect marketing, namely through websites, Facebook, and other applications. Educational marketing planning is carried out every time before the acceptance of new students including the formulation of the institution's vision and mission, market segmentation and placement, product positioning, and educational marketing pricing. Educational Marketing Organization is carried out to develop a marketing organization and develop its members. The implementation of educational marketing is carried out in a committed manner in accordance with the rules that have been planned including promotion and communication as well as delivery or distribution. Supervision of educational marketing is carried out to discuss oversight of annual plans, oversight of profitability, oversight of efficiency and oversight of educational marketing strategies as material for recommendations for further marketing. Promotion and communication is carried out through advertising/online, word of mouth, public relations, and direct marketing as well as delivery or distribution. The result of education marketing management is an increase in the number of applicants from year to year.